2013
DOI: 10.1007/s13197-013-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frying on the rheological and chemical properties of palm oil and its blends

Abstract: The aim of this research was to determine the changes in the physicochemical properties of palm oil and its blends by FTIR and rheological measurements. Application of heat produces some chemical compounds as impurities and even toxic compounds in oils and fats that give absorbance at different region. FTIR spectra of pure palm olein shows an absorbance at 3002 cm −1 whereas other pure oils show maximum absorption at around 3007 cm −1 due to C-H stretching vibration of cis-double bond (=C-H). By blending of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…According to the results obtained in the present study, the CO+PO blend exhibited heating stability upon prolonged time of the deep-fat frying process. This also was reported by Siddique et al (2015). Thus, it can be seen that much information about the stability of CO+PO after frying can be obtained from the entire range of FTIR spectra.…”
Section: Ftir Spectra Of Canola Oil and Its Blendssupporting
confidence: 75%
“…According to the results obtained in the present study, the CO+PO blend exhibited heating stability upon prolonged time of the deep-fat frying process. This also was reported by Siddique et al (2015). Thus, it can be seen that much information about the stability of CO+PO after frying can be obtained from the entire range of FTIR spectra.…”
Section: Ftir Spectra Of Canola Oil and Its Blendssupporting
confidence: 75%
“…In another study [107], the chemical properties of PO and its blend with SB, SU and CL and candlenut oils were compared in frying fish at 200 °C for 60 min. Due to higher saturation of PO (identified by means of Fourier transform infrared), it showed better oxidation stability and lower formation of trans isomers, when compared with the other used oils.…”
Section: Frying Fatmentioning
confidence: 99%
“…Besides coconut oil produced without going through a heating process so that the fatty acid content tends not to change. 20 So it can be concluded that VCO and CCO have high saponification values and are good for consumption.…”
Section: Chemical Analysis Of Vco and Ccomentioning
confidence: 99%
“…9 Their testimony of the benefits of VCO in overcoming several types of diseases, including: narrowing of blood vessels, canker sores, coughs, colds, hepatitis, diabetes, gout, high cholesterol, cramps, calcification, ulcers, pain in the knee, heart, ringworm, vaginal discharge, and haemorrhoid. 18,20 Moreover, VCO was using for diet therapy directly, and VCO is consumed while for CCO is used for cooking oil for in identifying quality21. Our result shows that, characterization of both VCO and CCO using physical and chemical parameters, the physical parameters: based on the results of research on VCO and CCO materials from both samples meet the physical requirements in accordance with the standard namely organoleptic covering the 35 color of VCO snown and CCO khaki and VCO and CCO typical odors coconut and to test its density in the results of the VCO study of 0.88 and 0.82 CCO with the standard according to SNI VCO 0.900 -0.913 and CCO 0.900.…”
Section: Chemical Analysis Of Vco and Ccomentioning
confidence: 99%